2022
DOI: 10.3390/polym14071347
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Efficiency of Externally Bonded CFRP Sheets for Shear Strengthening of RC Beam-Column Joints

Abstract: To develop feasible carbon fiber reinforced polymer (CFRP) retrofit schemes for the shear strengthening of real three-dimensional reinforced concrete (RC) beam-column joints, a series of parameters in relation to the contributions of the CFRP sheets externally bonded to joint panels was numerically investigated in this study. The parameters include CFRP reinforcement ratio, CFRP layout, transverse beam-to-joint panel width ratio, transverse beam-to-joint panel height ratio, location of transverse beam, and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The effect of a set of parameters related to the contribution of CFRP sheets that were externally attached to the joint was numerically investigated. The obtained results confirmed the effectiveness of the CFRP-strengthening technique with respect to a relatively wide range of considered parameters [20]. An investigation detailing RC beam-column joints strengthened with steel-reinforced polymer (SRP) systems and their seismic performance has been presented by Alessandro De Vita, and the results of an experimental campaign performed at the Laboratory of Materials and Structural Testing of the University of Salerno, Italy, have been published [21].…”
Section: Introductionsupporting
confidence: 70%
“…The effect of a set of parameters related to the contribution of CFRP sheets that were externally attached to the joint was numerically investigated. The obtained results confirmed the effectiveness of the CFRP-strengthening technique with respect to a relatively wide range of considered parameters [20]. An investigation detailing RC beam-column joints strengthened with steel-reinforced polymer (SRP) systems and their seismic performance has been presented by Alessandro De Vita, and the results of an experimental campaign performed at the Laboratory of Materials and Structural Testing of the University of Salerno, Italy, have been published [21].…”
Section: Introductionsupporting
confidence: 70%
“…Short-cut fibers are currently being considered as an approach for improving concrete, in terms of both strength and strain capacity [1][2][3][4], while unidirectional continuous fibers have been widely used for strengthening concrete structures [5][6][7]. Theoretically, the development of concrete microcracks can be prevented by the inclusion of short-cut fibers to some extent [8].…”
Section: Introductionmentioning
confidence: 99%
“…An important structural element is the beam-to-column junction area, which experiences stress concentration. In [ 35 ], several parameters have been defined regarding the contribution of CFRP sheets attached externally to connection panels. The results of numerical and experimental studies have shown the efficiency from 25% to 87% of various variants for strengthening the structure.…”
Section: Introductionmentioning
confidence: 99%